Decision-Making in Surgical Treatment for Posterior Inferior Cerebellar Artery (PICA) Aneurysm - Mohd Zamri, Sarah Atiqah; Hamzah, Nurfaten; Jayaraman, Thinesh Kumaran (Malaysian Journal of Medical Sciences, 2025)
Background: Posterior inferior cerebellar artery (PICA) aneurysm is rare. Endovascular treatment does not provide a decompressive effect, and the complex morphological features of PICA aneurysm make treatment approaches challenging. The objective of this study was to formulate a decision-making guide for PICA aneurysm according to location, based on an illustrative case and a review of the literature. Methods: From January 2022 until April 2023, a total of 157 aneurysm cases were treated using surgical and endovascular intervention. Fourteen patients were confirmed to have PICA aneurysm based on cerebral DSA/CTA. Demographic data, clinical characteristics, radiological findings, treatment plans, and outcomes were analysed. Outcomes were assessed using the modified Rankin Scale (mRS), with scores of zero to three considered good. Statistical analyses included Fisher’s exact test, Chi-square test, and McNemar test, where appropriate. Results: Of the total aneurysm cases, 8.9% were ruptured PICA aneurysms. Seven cases were located at the proximal PICA (P1 = 4 cases, P2 = 3), two cases at the mid PICA (P3), and five cases at the distal PICA (P4, P5). Out of 14 PICA aneurysms cases, nine were saccular, four were fusiform, and one was a dissecting aneurysm. Three patients underwent endovascular intervention (two saccular and one dissecting), while 11 underwent surgery (1 PICA–PICA in situ bypass with vertebral artery ligation, and 10 craniotomies with aneurysm clipping, with or without aneurysm reconstruction). Seven of 14 patients initially presented with good mRS scores, and at discharge, 10 patients had good scores. At discharge, two of three patients who had endovascular intervention had good mRS scores, and eight of 11 patients who went for surgery achieved good outcomes. Comparative analyses revealed no statistically significant associations between intervention type, aneurysm complexity, or location and outcome (P > 0.05). The McNemar test showed no significant difference between pre- and postoperative mRS scores (P = 0.25). However, a clinical trend toward improvement was observed, with the proportion of patients achieving good functional outcomes increasing from 50% before surgery to 71.4% at discharge. Conclusions: Favourable outcomes could be achieved when PICA aneurysm is treated with appropriate surgical strategies by experienced surgeons. Neurovascular surgeon must acquire knowledge of different surgical approaches and the technical skills required to perform these procedures.